Hyaluronic acid and beta cyclodextrins films for the release of corneal epithelial cells and dexamethasone. (15th June 2017) - Fiorica, Calogero; Palumbo, Fabio Salvatore; Pitarresi, Giovanna; Bongiovì, Flavia; Giammona, Gaetano
Highlights: Production a novel derivative of β-cyclodextrins. Chemical crosslinking between hyaluronic acid and β-cyclodextrins derivatives. Devices able to release both corneal epithelial cells and dexamethasone. Abstract: In this work we prepared hydrogels based on hyaluronic acid and β-cyclodextrins to sustain the release of both corneal epithelial cells and dexamethasone. This steroid is administered as eye drops several times per day to reduce the risk of rejection in the post operative period after the cornea transplantation and cell release techniques. Hydrogels were produced by crosslinking an amino derivative of hyaluronic acid, with the divinyl sulfone derivative of β-cyclodextrins, this last employed as a crosslinker and solubilizing agent. Drug release studies revealed that dexamethasone containing samples are able to extend the release of this drug for at least five days. Biological studies, conducted with human corneal epithelial cells, showed that it is possible to employ the hydrogels for the temporary seeding of the cells and their potential release onto the cornea.